PELAKSANAAN PEMBELAJARAN PAI PADA MASA PANDEMI COVID-19 DI SMAN 3 PAYAKUMBUH - Becky Sonata (El-Rusyd, 2021)
During the Covid-19 pandemic, students complained about online or online learning that was unfocused and negligent because the time allotted was more flexible. Meanwhile, for face-to-face learning, the time was shortened from 45 minutes to 30 minutes for 1 hour of lessons. With the limitations felt by students in the online learning process, the learning objectives are not achieved optimally. This study aims to determine the implementation of face-to-face, online, and blended learning PAI lessons during the Covid-19 pandemic at SMAN 3 Payakumbuh. classified in qualitative descriptive research. Data were collected using interviews and documentation. In carrying out Snowball Sampling interviews, namelytaking data sources which were initially small in number, eventually they became large. Key informants PAI educators and students. Principal supporting informants. The data analysis technique used is analyzing the data, data editing is done by making abstractions, and these units are then categorized as being done while coding. The school implements what is called a health protocol, starting from checking temperature, always washing hands, wearing masks, keeping a distance and bringing supplies from home. The implementation of online learning applications that are used by PAI educators in the teaching and learning process are WhatsApp, Google Classroom, Google Forms, Zoom, and Ruang Guru. The process of implementing learning starts from the introduction, delivery of material and closing, using applications and what is often used is WhatsApp. The implementation of Blended Learning during the Covid-19 pandemic was carried out with students divided into 2 groups. When group 1 does face-to-face learning, group 2 does online learning at the same time.